2006
DOI: 10.2341/04-173
|View full text |Cite
|
Sign up to set email alerts
|

Restorative Treatment Decision Making with Unaided Visual Examination, Intraoral Camera and Operating Microscope

Abstract: The use of an intraoral camera aided in the treatment of occlusal surfaces of molars. SUMMARYThis study assessed the restorative treatment options of the occlusal surfaces of teeth examined with unaided visual assistance, an intraoral camera and an operating microscope. Sixty-eight extracted human molars were mounted to perform mouth models with a premolar in contact on both sides. Four observers examined the models in a phantom head, which simulated clinical conditions, using three techniques: unaided visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 14 publications
0
28
1
3
Order By: Relevance
“…A histological evaluation was not made in their study; therefore, one could not estimate the accuracy of the results. Erten and others 15 reported no significant changes in treatment decision-making using an operating microscope at 16x magnification when histological evaluations were made, although there was an increase in true and false diagnosis rates. The current results are similar to the previous two reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A histological evaluation was not made in their study; therefore, one could not estimate the accuracy of the results. Erten and others 15 reported no significant changes in treatment decision-making using an operating microscope at 16x magnification when histological evaluations were made, although there was an increase in true and false diagnosis rates. The current results are similar to the previous two reports.…”
Section: Discussionmentioning
confidence: 99%
“…10,15 According to this model, all the teeth were asymptomatic, in acceptable occlusion with a DMFT score of 6, and they belonged to non-medicated, healthy patients with reasonably good oral hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical dental photography has a number of uses, which include: [1][2][3][4][5][6][7][8][9][10][11][12] Aim The aim of this study was to assess by means of a postal questionnaire the numbers of general dental practitioners (GDPs) who used clinical photography and for what application. Method The questionnaire was distributed to 1,000 randomly selected dentists in the UK with an explanatory letter and reply paid envelope.…”
Section: Introductionmentioning
confidence: 99%
“…Its impact on caries detection and treatment decision making has also been studied by various authors [8][9][10][11][12][13], as it is believed to allow for clearer visualisation of minute defects. However, some of these studies used high magnification values [10][11][12], others [9] have not correlated results with a gold standard [8]. To date there is no study reported which correlates the impact of magnification on visual-tactile detection of caries using ICDAS-II and a CPI-TN probe.…”
Section: Introductionmentioning
confidence: 99%